Integrative Psychotherapy for Depersonalization/Derealization: A Case Report of a Young Female - Tristi, Ranisa Kautsar; Maghfira Assyifa Amandienta Azzahra; Raisa Karima; Nisa Indah Pertiwi (Al Huwiyah: Journal of Woman and Children Studies, 2025)
Depersonalization/Derealization Disorder (DDD) is a dissociative condition characterized by feelings of detachment from oneself or one’s environment, often accompanied by functional impairment and comorbidity with other disorders. This study aim to demonstrate the application of integrative psychotherapy for a young adult female (20 years old) with DDD, severe depression, self-harming behaviour, suicidal ideation., and negative self-perceptions. Using a single case study design, the intervention followed an integrative protocol combining Cognitive Behavioural Therapy (CBT), Dialectical Behavioural Therapy (DBT) and Acceptance and Commitment Therapy (ACT) over 12 sessions, while examining the specific techniques and strategies employed in each therapeutic approach. Pre-test result showed severe levels of stress (33), anxiety (32), and depression (25). After 12 sessions, reassessment indicated a clinical decrease in score for stress (28), anxiety (26), and depression (20), alongside subjective improvements in emotional regulation, cognitive regulation.  and reduced dissociative frequency. This study confirms that staged integrative approach targeting specific symptom cluster can serve as an effective framework for addressing the clinical complexity of DDD. Further rigorous research is recommended to validate this framework and to consider any notables challenges encounter during the integrative psychotherapy sessions.